ORGANIC WASTE COMPOST PROCESSING USING ARDUINO-BASED AUTOMATED MACHINES - Mario Oktasa Sibarani; Kartika Kartika (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2022)
Compost is an important organic fertilizer in agriculture. Compost comes from weathering / decomposition of waste such as leaves. In the composting process, it can occur naturally but requires a longer time because during the decomposition process the temperature can change so that the performance of microorganisms that decompose waste decreases. The Arduino-based automatic machine is designed to maintain the temperature during the composting process. There are two types of systems used in composting machines. The first composting machine uses an automatic system that works every 3 hours to stir the waste in the tube while the second machine uses the system to work when the temperature detected by the DS18b20 sensor in the tube increases. In the second engine system the highest temperature is set at 38˚C. If the temperature in the tube increases and exceeds the temperature limit that has been set, the motor will work to stir the waste until the temperature in the tube drops. The results of the compost feasibility test on the first machine obtained a pH value of 5.84; Nitrogen 9.67%; Organic carbon 16.33%; C/N ratio 16.90; while the second machine obtained a pH value of 5.60; 8.60% Nitrogen; 17.89% organic carbon; C/N ratio 20.81